Penetapan Gubernur dan Wakil Gubernur Daerah Istimewa Yogyakarta Perspektif Fikih Siyâsah - Ahmad Pujianto (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2015)
Abstract: This article discusses about the Islamic political jurisprudence perspective against the determination of the Governor and Deputy Governor of Yogyakarta. Law No. 13 year 2012 on specialty of Yogyakarta as a Special Region provides a constitutional basis in establishing that the Governor and Deputy Governor of Yogyakarta was enthroned as Sultan and to the Deputy Governor as Adipati Paku Alam. However, in the case of succession of the Governor of Yogyakarta, there is an exception because it is basically a privilage of DIY that has been existing since Indonesia had not gotten its independent yet and it is also guaranteed by the constitution. The direct determination of Sultan and Paku Alam is intended to award to the diversity of customs and cultures among the people of different regions. It is so because the determination of the Governor and Deputy Governor of Yogyakarta should directly be addressed wisely by all circles.